THE REPRESENTATION OF NIETSCHE THOUGHT ON NOVELETTE KAPPA BY AKUTAGAWA RYUUNOSUKE - Amalia, Racmawati (Jurnal Ilmiah Mahasiswa FIB, 2013)
Kappa is one of Akutagawa Ryuunosuke masterpiece which is influenced of the thought of one of the biggest Germany pholisopher, Nietsche. This novelette are tells about the tales of patient number 23 whose said that he lived in Kappa world. After the witer read this novelette, rather than the typical satire of Akutagawa this novelette include lots of Nietsche thought.Nietzsche are ane of the existensialisme which is popular with his thought of “Death of God”. The writer in this studies used Ubermensch as the main idea because it’s more than enough to represent the thought of Nietsche which have been found  on novelette Kappa by Akutagawa Ryuunosuke.The result of this studies is that on novelette Kappa by Akutagawa Ryuunosuke there are many of the thought of Nietsche, that are Death of God, Will to Power, Eternal Return, and Perspektivisme.